The Novel Small Molecule STK899704 Promotes Senescence of the Human A549 NSCLC Cells by Inducing DNA Damage Responses and Cell Cycle Arrest - Park, Chan-Woo; Bak, Yesol; Kim, Min-Je; Srinivasrao, Ganipisetti; Hwang, Joonsung; Sung, Nak K.; Kim, Bo Yeon; Yu, Jae-Hyuk; Hong, Jin Tae; Yoon, Do-Young (Frontiers in Pharmacology, 2018)
The novel synthetic compound designated STK899704 (PubChem CID: 5455708) suppresses the proliferation of a broad range of cancer cell types. However, the details of its effect on lung cancer cells are unclear. We investigated the precise anticancer effect of STK899704 on senescence and growth arrest of A549 human non-small cell lung cancer (NSCLC) cells. STK899704 affected NSCLC cell cycle progression and decreased cell viability in a dose-dependent manner. Immunofluorescence staining revealed that STK899704 destabilized microtubules. Cell cycle analysis showed an increase in the population of NSCLC cells in the sub-G1 and G2/M phases, indicating that STK899704 might cause DNA damage via tubulin aggregation. Furthermore, we observed increased mitotic catastrophe in STK899704-treated cells. As STK899704 led to elevated levels of the p53 pathway-associated proteins, it would likely affect the core DNA damage response pathway. Moreover, STK899704 promoted senescence of NSCLC cells by inducing the p53-associated DNA damage response pathways. These findings suggest that the novel anti-proliferative small molecule STK899704 promotes cell death by inducing DNA damage response pathways and senescence after cell cycle arrest, being a potential drug for treating human lung cancers.